2018
DOI: 10.7554/elife.33116
|View full text |Cite
|
Sign up to set email alerts
|

Sorting of a multi-subunit ubiquitin ligase complex in the endolysosome system

Abstract: The yeast Dsc E3 ligase complex has long been recognized as a Golgi-specific protein ubquitination system. It shares a striking sequence similarity to the Hrd1 complex that plays critical roles in the ER-associated degradation pathway. Using biochemical purification and mass spectrometry, we identified two novel Dsc subunits, which we named as Gld1 and Vld1. Surprisingly, Gld1 and Vld1 do not coexist in the same complex. Instead, they compete with each other to form two functionally independent Dsc subcomplexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 62 publications
2
40
0
Order By: Relevance
“…Gld1 binding sorts the Dsc complex to the Golgi and to endosomes, while Vld1 diverts the Dsc complex from the Golgi via the AP‐3 pathway directly to the limiting membrane of the vacuole. In gld1Δ mutants, the Dsc complex is exclusively detected on the limiting membrane of vacuoles (Yang et al , ). Disrupting Gld1 resulted in GFP‐Orm2 accumulation at the ER and post‐ER compartments (Fig A, fully penetrant phenotype, n = 153 cells), similar to tul1∆ .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gld1 binding sorts the Dsc complex to the Golgi and to endosomes, while Vld1 diverts the Dsc complex from the Golgi via the AP‐3 pathway directly to the limiting membrane of the vacuole. In gld1Δ mutants, the Dsc complex is exclusively detected on the limiting membrane of vacuoles (Yang et al , ). Disrupting Gld1 resulted in GFP‐Orm2 accumulation at the ER and post‐ER compartments (Fig A, fully penetrant phenotype, n = 153 cells), similar to tul1∆ .…”
Section: Resultsmentioning
confidence: 99%
“…The deletion of Vld1 did not alter the ER localization of GFP‐Orm2 (Fig A). In vld1Δ mutants, the Dsc complex is no longer detected on the limiting membrane of the vacuole, but still localizes to Golgi and endosomes (Yang et al , ). These results suggested that the Gld1‐Dsc complex prevented the accumulation of Orm2 on endosomes and Golgi.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation is at odds with work in budding yeast, where Tul1 substrates appeared to be degraded exclusively via the lysosome (Migliano & Teis, ). Moreover, a recent study (Yang et al , ) describing two mutually exclusive Dsc cofactors, Vld1 and Gld1, has defined Dsc complexes with distinct subcellular distribution: While Gld1‐containing Dsc complexes localize to Golgi/endosomes, Vld1‐containing complexes are found at the membrane of the vacuole, the yeast equivalent of the lysosome (Yang et al , ).…”
Section: Comparison Of Er‐associated (Erad) and Endosome/golgi‐associmentioning
confidence: 99%